The effect of biophilic design on customer's subjective well-being in the hotel lobbies. (September 2022) - Song, Chengli; Ali, Faizan; Cobanoglu, Cihan; Nanu, Luana; Lee, Seung Hyun Jenna
Abstract: The current study explored customers' psychological responses caused by biophilic design in the context of hotels and investigated the relationship between self-image congruity, delight, and subjective well-being of hotel guests. Based on a 2 × 2 between-subject experimental design, 390 participants were randomly assigned to different manipulated conditions. Data were subjected to ANOVA, and the results show non-significant differences between biophilic elements and customer psychological reactions and subjective well-being. Moreover, the findings evoked that customer self-image congruity and delight evoked subjective well-being through regression analysis. Theoretical and managerial implications are also discussed.